2016
DOI: 10.1186/s12974-016-0541-7
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin inhibits lipopolysaccharide-induced inflammation in microglial cells and attenuates microglial activation in lipopolysaccharide-treated mice

Abstract: BackgroundOveractivated microglia is involved in various kinds of neurodegenerative diseases. Suppression of microglial overactivation has emerged as a novel strategy for treatment of neuroinflammation-based neurodegeneration. In the current study, anti-inflammatory effects of oxytocin (OT), which is a highly conserved nonapeptide with hormone and neurotransmitter properties, were investigated in vitro and in vivo.MethodsBV-2 cells and primary microglia were pre-treated with OT (0.1, 1, and 10 μM) for 2 h foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
139
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(156 citation statements)
references
References 52 publications
(71 reference statements)
5
139
1
3
Order By: Relevance
“…The GluN2B subunit of NMDA receptors is thought to exert a main channel function in the brain . Activation of NMDA receptors, including the GluN2B subunit, induces Ca 2+ influx, thus augmenting intracellular Ca 2+ levels and activating CaMKs . In the present study, we observed that ketamine reduced LPS‐induced Ca 2+ levels and CaMK II phosphorylation, thus inhibiting LPS‐mediated inflammation in BV2 cells.…”
Section: Discussionsupporting
confidence: 63%
“…The GluN2B subunit of NMDA receptors is thought to exert a main channel function in the brain . Activation of NMDA receptors, including the GluN2B subunit, induces Ca 2+ influx, thus augmenting intracellular Ca 2+ levels and activating CaMKs . In the present study, we observed that ketamine reduced LPS‐induced Ca 2+ levels and CaMK II phosphorylation, thus inhibiting LPS‐mediated inflammation in BV2 cells.…”
Section: Discussionsupporting
confidence: 63%
“…Prolactin has been found to enhance the inflammatory response and proliferation of glia following a traumatic brain injury (Möderscheim et al, 2007), and oxytocin administration has been found to alleviate tissue damage in various animal models of injury (Akdemir et al, 2014; Houshmand et al, 2009; Karelina et al, 2011). The protective mechanisms by which prolactin and oxytocin act may be related to a decrease in pro-inflammatory cytokines from microglia, macrophages, and endothelial cells (Akman et al, 2015; Szeto et al, 2008; Tug˘tepe et al, 2013; Yuan et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…In general, microglia play an important role in neuroprotection, especially confrontation with pathogens from the external environment; however, overexpression of microglia causes many key cellular responses that can cause diseases by inducing pro-inflammatory mediators such as NO, PGE 2 and TNF-α (Lee et al, 2011). Therefore, a promising therapeutic strategy used for neurodegenerative diseases was focused on blocking microglial activation processes (Kim and Joh, 2006;Yuan et al, 2016). Recently, numerous studies have reported that traditional Chinese medicine exert neuroprotective effects through suppressing microglial activation, and their effects have been elevated to have the potential to treat neurodegenerative diseases Wang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%